Legal Protection for Consumers Who Suffer Losses Due to Goods Purchased Online Not in Accordance with the Agreement - Angelina Kristin Laoly, Grace; Esther, July; Hertati Gultom, Meli (Greenation International Journal of Law and Social Sciences, 2024)
This study aims to analyze legal protections for consumers who suffer losses due to goods purchased online not in accordance with agreements. Using normative legal research methods and case studies, this study examines consumer protection regulations based on Law Number 8 of 1999 concerning Consumer Protection (UUPK). The results of the study show that consumers have the right to goods in accordance with the agreement and are entitled to compensation in the event of a violation. However, challenges such as the difficulty of claiming and returning goods procedures are still an obstacle. This study also found that the non-litigation mechanism through BPSK provides a fast and cheap alternative to dispute resolution. Effective law enforcement and supervision of business actors on e-commerce platforms are urgently needed to improve consumer protection in digital transactions.